Conceptualising and measuring consumer-based brand–retailer–channel equity. (March 2016) - Londoño, Juan Carlos; Elms, Jonathan; Davies, Keri
Abstract: This paper presents a critical review and synthesis of the extant literature which underscores the complexities of conceptualising and measuring the synergies created by brand, retailer, and channel equity. To this end, the concept of Consumer-based Brand–Retailer–Channel Equity (CBBRCE) is developed. The concept and its measurement are subsequently tested empirically using survey data and structural equation modelling with path-PLS. The results confirm that CBBRCE is created by CBBRC Awareness, Quality and Loyalty. The paper concludes with a discussion of the managerial implications of CBBRCE, and signals areas for further academic research. Highlights: A literature review presents how brand, retailer and channel are currently measured. Develop the concept of Consumer-based Brand–Retailer–Channel Equity (CBBRCE). CBBRCE is tested empirically using survey data and PLS SEM. CBBRCE is created by CBBRC Awareness, Quality and Loyalty. CBBRCE implies the development of alliances between manufacturer brands and retailers.